The effect of adversity quotient and marked orientation on firm perfomance through the mediating role of entrepreneurial orientation in small and medium-sized textile industries in Indonesia - Irawan, Towaf Totok (2024)
Small and medium-sized textile industries are facing competition constraints and the Covid-19 pandemic. The impact can be seen from its increasingly decreased contribution to gross domestic product and export performance. This situation has implications for the industrial sustainability in which some industries can survive and others cannot.The purpose of this study is to respond to the research needs, namely, to examine the effects of adversity quotient, entrepreneurial orientation, and market orientation on firm performance in small and medium-sized textile industries in Indonesia. This study used the theoretical model based on the resource-based view approach. Quantitative survey methods were employed, while questionnaires were used to collect data from a total of 287 respondents from small and medium-sized textile and textile product industries. The data were analyzed using a statistical technique, namely structural equation modeling - partial least squares to examine the direct and indirect effects of exogenous and endogenous variables. The findings show a positive and significant effect of adversity quotient on firm performance; adversity quotient on entrepreneurial orientation; entrepreneurial orientation on firm performance; and market orientation on entrepreneurial orientation, while market orientation has a negative and significant effect on firm performance The mediating role of entrepreneurial orientation is partially shown in the relationship between adversity quotient and firm performance, and fully shown in the relationship between market orientation and firm performance. These results provide evidence that supports the theoretical model of resource-based view, which explains the relationship between adversity quotient, market orientation, entrepreneurial orientation and their effect on the performance of small-scale textile industries. These findings have theoretical and practical implications for small-scale textile industries in Indonesia. This study presents limitations and recommendations